Model of the U.S. Current Account. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
This paper presents an econometric model of U.S. current account transactions. The model is used to analyze the factors behind the deterioration in the U.S. external position during the 1980s and to examine the sensitivity of the U.S. current account balance to changes in factors which are its major determinants. The results suggest that the appreciation of the U.S. dollar and relatively faster economic growth in the United States account for most of the rise in the U.S. external deficit. The results also indicate that the depreciation of the dollar since March 1985 has contributed to a substantial improvement in the U.S. current account balance relative to what it otherwise might have been.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet